2013
DOI: 10.1093/europace/eut260
|View full text |Cite
|
Sign up to set email alerts
|

Uric acid is associated with future atrial fibrillation: an 11-year follow-up of 6308 men and women--the Tromso Study

Abstract: This prospective population-based cohort study showed that baseline SUA was associated with an increased risk for future AF in both sexes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 29 publications
3
58
0
1
Order By: Relevance
“…A previous study from our group showed that elevated baseline UA is associated with increased risk of atrial fibrillation, 27 and another study recently demonstrated that LA size ≥2.8 cm/m 2 was significantly associated with increased risk of incident atrial fibrillation.…”
Section: Left Atrium Sizementioning
confidence: 71%
“…A previous study from our group showed that elevated baseline UA is associated with increased risk of atrial fibrillation, 27 and another study recently demonstrated that LA size ≥2.8 cm/m 2 was significantly associated with increased risk of incident atrial fibrillation.…”
Section: Left Atrium Sizementioning
confidence: 71%
“…44 Another study reported that hyperuricemia was a significant predictor of stroke in a population of patients suffering from atrial fibrillation. 45 UA might potentially trigger arrhythmia as an endogenous danger signal.…”
Section: Discussionmentioning
confidence: 99%
“…Whether or not gout is present, elevated SUA level is associated with cardiovascular diseases such as hypertension [14], coronary heart disease [19][20][21], AF [24,26], and stroke [22,23]. Previous studies have suggested that this correlation could be due to endothelial dysfunction, local oxidant generation, elevated vascular smooth cell proliferation, and reduced vascular nitric oxide production induced by SUA [28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a correlation was recently detected between hyperuricemia and the development of new-onset AF and increased risk of ischemic stroke in patients with AF [24][25][26][27]. Previous studies suggested associations between hyperuricemia and endothelial dysfunction [28], local oxidant generation, and elevated circulating levels of systemic inflammatory mediators [29,30].…”
Section: Introductionmentioning
confidence: 96%